Near-infrared/visible-emitting nanosilica modified with silylated Ru(II) and Ln(III) complexes - Sábio, Rafael Miguel [UNESP]; Santagneli, Silvia Helena [UNESP]; Gressier, Marie; Caiut, José Maurício Almeida; Pazin, Wallance Moreira; Ribeiro, Sidney José Lima [UNESP]; Menu, Marie-Joëlle (IOP Publishing, 2020)
Three luminescent silica-based nanohybrids were fabricated by grafting of silylated Ru(II) and Nd/Yb(III) complexes onto mesoporous silica nanoparticles obtained by microemulsion method. The prepared nanohybrids were characterized by Fourier transform-Raman spectroscopy, solid state-nuclear magnetic resonance, high resolution-transmission electron microscopy and scanning and transmission electron microscopy techniques. The chemical integrity and the grafting of all complexes inside MSNs nanopores as well as a good distribution of metal complexes onto MSNs surface were achieved for all nanohybrids. Photophysical results revealed that by monitoring the excitation on Ru(II) moieties from SiO 2-RuNd and SiO 2-RuYb nanohybrids, the sensitization of NIR-emitting Nd/Yb(III) ions were successfully detected via energy transfer processes. Energy transfer rates (k EnT) of 0.20 × 107 and 0.11 × 107 s-1 and efficiencies of energy transfer (η EnT) of 40% and 27.5% were obtained for SiO 2-RuNd and SiO 2-RuYb nanohybrids, respectively. These results confirm the preparation of promising dual (near-infrared/visible)-emitting silica-based nanohybrids as new nanotools for applications as nanosensores and nanomarkers.